Strong-field driven dynamics of metal and dielectric nanoparticles - Powell, Jeffrey (Kansas State University, 2017)
The motion of electrons in atoms, molecules, and solids in the presence of intense electromagnetic radiation is an important research topic in physics and physical chemistry because of its fundamental nature and numerous practical applications, ranging from precise machining of materials to optical control of chemical reactions and light-driven electronic devices. Mechanisms of light-matter interactions critically depend on the dimensions of the irradiated system and evolve significantly from single atoms or molecules to the macroscopic bulk. Nanoparticles provide the link between these two extremes. In this thesis, I take advantage of this bridge to study light-matter interactions as a function of nanoparticle size, shape, and composition. I present here three discrete, but interconnected, experiments contributing to our knowledge of nanoparticle properties and their response to intense, short-pulsed light fields. First, I investigate how individual nanoparticles interact with each other in solution, studying their temperature-dependent solubility. The interaction potential between 5.5nm gold nanoparticles, ligated by an alkanethiol was found to be -0.165eV, in reasonable agreement with a phenomenological model. The other two experiments explore ultrafast dynamics driven by intense femtosecond lasers in isolated, gas-phase metallic and dielectric nanoparticles. Photoelectron momentum imaging is applied to study the response of gold, silica, and gold-shell/silica-core nanoparticles (ranging from single to several hundred nanometers in size) with near-infrared (NIR), 25 fs laser pulses in the intensity range of 10¹¹ - 10¹⁴ W/cm². These measurements, which constitute the bulk of my graduate work, reveal the complex interplay between the external optical field and the induced near-field of the nanoparticle, resulting in the emission of very energetic electrons that are much faster than those emitted from isolated atoms or molecules exposed to the same light pulses. The highest photoelectron energies (“cutoffs”) were measured as a function of laser intensity, nanoparticle material and size. We found that the energy cutoffs increase monotonically with laser intensity and nanoparticle size, except for the gold/silica hybrid where the plasmon resonance response modifies this behavior at low intensities. The measured photoelectron spectra for metallic nanoparticles display a large energy enhancement over silica. Finally, the last part of this thesis explores the possibility to apply time-resolved x-ray scattering as a probe of the ultrafast dynamics in isolated nanoparticles driven by very intense (~10¹⁵ W/cm²) NIR laser radiation. To do this, I developed and built a nanoparticle source capable of injecting single, gas-phase nanoparticles with a narrow size distribution into the laser focus. We used femtosecond x-ray pulses from an x-ray free electron laser (XFEL) to map the evolution of the laser-irradiated nanoparticle. The ultrafast dynamics were observed in the single-shot x-ray diffraction patterns measured as a function of delay between the NIR and x-ray pulses, which allows for femtosecond temporal and nanometer spatial resolution. We found that the intense IR laser pulse rapidly ionizes the nanoparticle, effectively turning it into a nanoplasma within less than a picosecond, and observed signatures of the nanoparticle surface softening on a few hundred-femtosecond time scale.
Keywords: Nanoparticles; Strong-field; Ultrafast; Femtosecond laser; Solubility; Free electron laser